The EU's open strategic autonomy in the field of pharmaceuticals: Overcoming import dependencies for antibiotics through the EU authority HERA - Michael Bayerlein (Stiftung Wissenschaft und Politik (SWP), 2023)
The COVID-19 pandemic and war in Ukraine have highlighted the dependence of the European Union (EU) on individual trading partners. One of the tasks of the European Commission's new Directorate-General, the Health Emergency Preparedness and Response Authority (HERA), established in 2021, will therefore be to contribute to the EU's 'open strategic autonomy' by identifying and eliminating import dependencies in the field of pharmaceuticals. HERA's work thus aligns with current EU efforts to reduce concentrated import risks. Here, three aspects of this work are particularly important: the identification of dependencies, the development of strategies to overcome them and the incorporation of these strategies within global health governance.
Keywords: 320; Health Emergency Preparedness and Response Authority; HERA; Biomedical Advanced Research and Development Authority; BARDA; Critical Raw Materials Act; CRMA; European Raw Materials Alliance; ERMA; European Chips Act; Global Antibiotic Research & Development Partnership; GARDP; Innovative Health Initiative; IHI; Incubator for Antibacterial Therapies in Europe; INCATE; Minerals Security Partnership; MSP; Raw Materials Investment Platform; RMIP; Covid-19; NextGenerationEU; rescEU; UN Comtrade; European Centre for Disease Prevention and Control; ECDC; Important Project of Common European Interest; IPCEI; pharmaceuticals; antibiotics; Active Pharmaceutical Ingredients; API; Finished Pharmaceutical Product; FPP; supply chains; global health governance; Reshoring; friend-shoring